RACI Matrix Design for Managing Stakeholders in Project Case Study of PT. XYZ - Rahmad Dwi Putra Suhanda; Devi Pratami (School of Industrial and System Engineering, Telkom University, 2021)
Stakeholders are one of the most significant factors in the success of a project. The creation of good team performance in a project is caused by clear work responsibilities given to each project stakeholder so that stakeholders have responsibility for their work and can complete their work correctly. The responsibility assignment matrix is ​​a method for managing the roles of each resource and describing the relationship between jobs for each job in the project, which is classified into four parts, namely Responsible, Assignment, Consult, and Informed. In this paper, a matrix will be designed to manage the work assignments of each stakeholder involved in the case of delays in project completion at PT. XYZ uses the RACI Matrix method as a guide. The results of the work assignment matrix design in the case study project of PT. XYZ shows that 12 stakeholders are grouped into four classifications according to the RACI components, which are arranged based on the level of interest and responsibility of each stakeholder to the project.